Detection of Clostridium Tyrobutyricum in Milk to Prevent Late Blowing in Cheese by Automated Ribosomal Intergenic Spacer Analysis. Issue 10 (8th October 2013) - Panelli, Simona; Brambati, Eva; Bonacina, Cesare; Feligini, Maria
Abstract: Clostridium tyrobutyricum has been identified as the main causal agent of the late blowing defect in cheese, with major effects on quality and commercial value. In this work, for the first time, we applied automated ribosomal intergenic spacer analysis (ARISA) approach to diagnose the presence of C. tyrobutyricum in raw milk before cheesemaking. A species‐specific primer set was designed and used for this original application of the ARISA. Sensitivity of detection, reproducibility of the fluorescent PCR assay, and repeatability of the capillary electrophoretic analysis of amplicons were evaluated using DNA extracted from milk added with known amounts of C. tyrobutyricum genome copies, ranging from 3 × 10 6 to 3. Results indicated that the sensitivity of the technique permits to detect the bacterium in all the samples. The reproducibility, evaluated by analyzing 3 sets of serial dilutions, resulted satisfactory, with little deviation within PCR reactions amplifying the same starting amount of template (standard deviations ≤ 0.1, coefficients of variation ≤ 3%). The peaks' fluorescence displayed an evident correspondence with the number of genome copies contained in each dilution. The capillary electrophoretic analysis, tested by running a single PCR product per dilution point in 10 repeats, resulted efficient and highly repeatable, with excellent coefficients of variation ≤ 2% and standard deviations ≤ 0.1 in all the sample sets. This application of ARISA gives good estimates of the total C. tyrobutyricum DNA content allowing a specific, fine‐scale resolution of this pollutant species in a complex system as milk. A further advantage linked to the automatization of the process.